(untitled) (Nonconventional Technologies Review, 2020)
Pandemics, earthquakes, floods are well known as crisis phenomena along with political crises. The current crisis represented by the Coronavirus pandemic can be characterized by the underlying causes of its production and the forms of manifestation as defined by volatility, uncertainty, complexity and ambiguity specific to the VUCA concept which means a specific nature with a wide and rapid dynamics of change, with the misunderstanding of problems and events, which are unknown in a context of the complexity of the forces and factors involved without knowing causes and effects and misunderstandings.